Clinical Efficacy of Repeated Applications of Local Drug Delivery and Adjunctive Agents in Nonsurgical Periodontal Therapy: A Systematic Review - Oi Leng Tan; Syarida Hasnur Safii; Masfueh Razali (MDPI AG, 2021)
The aim of this systematic review is to compare the clinical efficacy of repeated applications of local drug delivery and adjunctive agents (LDAs) in nonsurgical periodontal therapy (NSPT) compared to subgingival mechanical debridement (SMD) alone. The Cochrane Central Register of Controlled Trials, MEDLINE, PubMed, EMBASE, Web of Science, hand-searched literature and grey literature databases were searched for randomized controlled clinical trials (RCTs) with a minimum of 6-month follow-up. The outcomes of interest were changes in probing pocket depth and clinical attachment level as well as patient-centred outcomes. Of 1094 studies identified, 16 RCTs were included in the qualitative analysis. Across 11 different adjuncts analysed, only two studies utilizing minocycline gel/ointment and antimicrobial photodynamic therapy (aPDT) with indocyanine green photosensitizer had statistically significant differences in primary outcomes when compared to their control groups. Only one study on aPDT methylene blue 0.005% had compared single versus multiple applications against its control group. A mean range of 0.27-3.82 mm PD reduction and −0.09-2.82 mm CAL gain were observed with repeated LDA application. Considerable clinical heterogeneity and methodological flaws in the included studies preclude any definitive conclusions regarding the clinical efficacy of repeated LDA applications. Future RCTs with a direct comparison between single and repeated applications should be conducted to confirm or refute the clinical advantages of repeated LDA application in the nonsurgical management of periodontitis.